A Printed Dipole Antenna for 5G Millimeter Wave Application. Issue 2 (March 2021) - He, Xingyi
Abstract: An essential point of the technology in the 5th generation (5G) communications is to utilize the available spectrum in high frequencies beyond 20GHz, whose corresponding wavelengths reach a relatively small millimeter magnitude. To cope with the challenge of such short wavelengths, this paper has proposed a printed dipole antenna with a geometric structure that two dipole arms are patched on opposite sides of a FR4 substrate fed by a microstrip line and triangular balun. Simulations have shown that the proposed antenna possesses a relatively effective performance operated at 21.6 ∼ 25.4GHz with a maximum gain of 1.62dB. Additionally, the impact of some geometric parameters, such as the sizes of dipole arms and triangle baluns, are also discussed in this paper.